2019
DOI: 10.1111/iju.14065
|View full text |Cite
|
Sign up to set email alerts
|

Risks of interstitial cystitis among patients with systemic lupus erythematosus: A population‐based cohort study

Abstract: Abbreviations & Acronyms aHR = adjusted hazard ratio CI = confidence interval DM = diabetes mellitus HTN = hypertension IC = interstitial cystitis ICD-9 CM = International Classification of Diseases-9th Revision-Clinical Modification IR = incidence rate IRR = incidence rate ratio NHI = National Health Insurance NHIRD = National Health Insurance Research Database NTD = New Taiwan Dollars PY = person-year SLE = systemic lupus erythematosus Correspondence: Ming-Ping Objective: To investigate whether the risk of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…A nationwide population-based cohort study of 11,526 patients with primary Sjogrens syndrome in Taiwan revealed an increased risk of BPS/IC in this cohort, with a hazard ratio of 2.34 (95% CI 1.59-3.44, p < 0.01) [45]. A similar study revealed a higher incidence of BPS/IC in patients with systemic lupus erythematosus, with a hazard ratio of 2.45 (95% CI 1.57-3.27, p < 0.05) [46]. Further research is required to determine whether phenotypes of BPS/IC associated with autoimmune conditions could benefit from targeted immunomodulatory therapies [47].…”
Section: Phenotype Based On Co-existing Somatic Conditionssupporting
confidence: 60%
“…A nationwide population-based cohort study of 11,526 patients with primary Sjogrens syndrome in Taiwan revealed an increased risk of BPS/IC in this cohort, with a hazard ratio of 2.34 (95% CI 1.59-3.44, p < 0.01) [45]. A similar study revealed a higher incidence of BPS/IC in patients with systemic lupus erythematosus, with a hazard ratio of 2.45 (95% CI 1.57-3.27, p < 0.05) [46]. Further research is required to determine whether phenotypes of BPS/IC associated with autoimmune conditions could benefit from targeted immunomodulatory therapies [47].…”
Section: Phenotype Based On Co-existing Somatic Conditionssupporting
confidence: 60%
“…Furthermore, the lower urinary tract symptoms in these patients resemble those in patients with IC/BPS with Hunner lesions 34,35 . In addition, female preponderance and an increased prevalence of comorbid systemic autoimmune disorders are well‐known epidemiological features of IC/BPS 36–38 . Collectively, this evidence strongly suggests the possible autoimmune nature of IC/BPS with Hunner lesions.…”
Section: Pathophysiology Of Ic/bpsmentioning
confidence: 75%
“…The study indicated that twin similarity is suggestive of a genetic component to the etiology of IC/BPS in women. Further, IC/BPS has many features similar to those of autoimmune diseases, which display complicated gene-environment interactions [18][19][20] .The influence of environmental factors on IC/BPS and how to avoid such influence warrant further investigation. Further, the recruited patients with IC/BPS in this study had an average onset time of 6 years before their diagnosis was confirmed.…”
Section: Discussionmentioning
confidence: 99%